What is driving oil futures prices? Fundamentals versus speculation - Isabel Vansteenkiste (European Central Bank (ECB), 2011)
In this paper we analyse the relative importance of fundamental and speculative demand on oil futures price levels and volatility. In a first step, we present a theoretical heterogeneous agent model of the oil futures market based on noise trading. We use the model to study the interaction between the oil futures price, volatility, developments in underlying fundamentals and the presence of different types of agents. We distinguish between commercial traders (who are physically involved in oil) and non-commercial traders (who are not involved physically with oil). Based on the theoretical model we find that a multiplicity of equilibria can exist. More specifically, on the one hand, if we have high fundamental volatility, high uncertainty about future oil demand, and the oil price deviation from fundamentals or the price trend is small, we will only have commercial traders entering the market. On the other hand, if a large unexpected shock to the oil spot price occurs then all traders will enter the market. In a next step, we empirically test the model by estimating a markov-switching model with time-varying transition probabilities. We estimate the model over the period January 1992 - April 2011. We find that up to 2004, movements in oil futures prices are best explained by underlying fundamentals. However, since 2004 regime switching has become more frequent and the chartist regime has been the most prominent.
Keywords: D84; Q33; Q41; G15; 330; Markov switching models; Oil prices; Speculation